Potential of Cosmos caudatus Kunth. extract as a natural food sanitiser - Yusoff, N.A.H.; Rukayadi, Y.; Abas, F.; Khatib, A.; Hassan, M. (Universiti Putra Malaysia, 2024)
Bacterial growth in food sources after harvesting and during food manufacturing has emerged as a major agricultural concern. Currently, several chemical preservatives have been added to foods to prevent or inhibit bacterial growth. These phenomena, however, become a concern when consumers begin to demand the safety of the food they consume, thus resulting in a search for natural plant extracts as an alternative. The antimicrobial activity of Cosmos caudatus leaf extract against six food pathogens was thus investigated in the present work. The disc-diffusion test, the minimum inhibitory concentration (MIC), and the minimum bactericidal concentration (MBC) tests were used to determine the antibacterial potential. Time-kill kinetics were used to determine their killing endpoints at various incubation times. Thereafter, Bacillus cereus was selected as a representative bacterium to be viewed under the light sheet electron microscope (LSEM) to observe the morphological changes. For the application as a sanitiser, different concentrations of C. caudatus extract were applied to chicken meat and oyster mushroom to determine bacterial reduction and sensory acceptability. The toxicity test using brine shrimp lethality assay was also performed to determine the toxicity level of C. caudatus extract. Results showed that C. caudatus extract contain five major peaks of flavonoids. In the antibacterial test, all tested pathogens were inhibited, with B. cereus being the most susceptible, with a significant reduction time of more than 3 log10 at 3.125 mg/mL. Under LSEM, the population of B. cereus was reduced, and the shape was wrinkled. In the application, C. caudatus extract at 0.05% for 5 min treatment time was chosen as the best formulation, whereas the brine shrimp tests showed that C. caudatus extract was safe for human consumption (LC50: 3.54 mg/mL). In conclusion, C. caudatus extract could have the potential to be further explored as a natural food sanitiser.